2018
DOI: 10.4049/jimmunol.1701446
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 Regulates NF-κB Activation via Association with Breakpoint Cluster Region and Casein Kinase II

Abstract: We recently reported that NF-κB-mediated inflammation caused by breakpoint cluster region (BCR) is dependent on the α subunit of casein kinase II (CK2α) complex. In the current study, we demonstrate that presenilin 1 (Psen1), which is a catalytic component of the γ-secretase complex and the mutations of which are known to cause familial Alzheimer disease, acts as a scaffold of the BCR-CK2α-p65 complex to induce NF-κB activation. Indeed, Psen1 deficiency in mouse endothelial cells showed a significant reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…In cytokine-induced RA models, 100 ng of human IL-6 (Toray Industries), 100 ng of mouse IL-17A (R&D Systems), or saline was injected into the ankle joints of F759 mice, as described previously (24). In some experiments, lentivirus particles carrying shRNA specific for TMEM147 (Sigma-Aldrich) or a scrambled sequence (Sigma-Aldrich) were injected into the ankle joints of mice (12,17,19,(24)(25)(26)(27). Anti-TMEM147 antibodies (Sigma-Aldrich) were injected into the ankle joints of mice at a dosage of 2 μg per day.…”
Section: Methodsmentioning
confidence: 99%
“…In cytokine-induced RA models, 100 ng of human IL-6 (Toray Industries), 100 ng of mouse IL-17A (R&D Systems), or saline was injected into the ankle joints of F759 mice, as described previously (24). In some experiments, lentivirus particles carrying shRNA specific for TMEM147 (Sigma-Aldrich) or a scrambled sequence (Sigma-Aldrich) were injected into the ankle joints of mice (12,17,19,(24)(25)(26)(27). Anti-TMEM147 antibodies (Sigma-Aldrich) were injected into the ankle joints of mice at a dosage of 2 μg per day.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that the IL-6 amplifier is triggered by the simultaneous activation of two transcriptional factors, NFκB and STAT3, in non-immune cells, and that this activation is associated with various inflammatory pathologies (7,8,(11)(12)(13)(14)(15)(16)(17)(18)(19). The co-activation of NFκB and STAT3 Takada et al p. 14 synergistically promotes the production of various NFκB-target genes including IL-6 (7,8,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: The Il-6 Amplifier Is Activated In Tubular Cells Of Caamr Pa...mentioning
confidence: 99%
“…The co-activation of NFκB and STAT3 enhances NFκB signaling to synergistically promote the production of various NFκB-driven inflammatory mediators including IL-6, chemokines and growth factors, and induce chronic inflammation in the affected tissues (8)(9)(10). Inhibition of the IL-6 amplifier significantly improves pathological outcomes in mouse disease models including allogenic transplantation rejection, multiple sclerosis, dermatitis, uveoretinitis and rheumatoid arthritis (7,8,(11)(12)(13)(14)(15)(16)(17)(18)(19). Consistently, its activation is observed in human allogeneic lung transplantation with chronic rejection phenotypes, and target molecules of the IL-6 amplifier are elevated in patients with inflammatory diseases such as atherosclerosis, multiple sclerosis, lung transplant rejection, keloid, and rheumatoid arthritis (7,13,20).…”
Section: Introductionmentioning
confidence: 99%
“…Promoter analysis and functional studies link expression of each of these genes to regulation by NF-κB (8285). In some cases, products from AD-associated genes, such as presenilin 1, have also been shown to mediate reciprocal activation of NF-κB (RelA/p65 containing dimers) in putative pro-inflammatory cascades (86).…”
Section: Alzheimer's Diseasementioning
confidence: 99%